'Japanese and the major are incompatible': institutional reasons for dropping Japanese at the transition from secondary to tertiary education. Issue 4 (2nd October 2017) - Oshima, Ryoko; Harvey, Sharon
Abstract : With anglophone countries now experiencing unprecedented levels of ethnic and linguistic diversity, it is considered increasingly important that young people learn to communicate in ways which are effective for the multilingual and intercultural contexts they live in, will work in and will travel to. One of the key vehicles for promoting and engendering this capability is the learning of languages additional to English. However, just as language learning is being called upon to deliver education for citizenship in super-diverse contexts, many countries are experiencing a decline in the numbers of students studying languages. A particularly important time for decision-making and reassessment of whether to continue with language learning is the transition point between secondary and tertiary education. This paper takes Japanese learning in New Zealand as a case study to illustrate the issues languages students struggle with as they negotiate this transition. Japanese is an important additional language of education, particularly in the Asia Pacific region, where Japan has been seen as a major political and economic power through much of the post-Second World War period. In a previous study, we analysed the mainly affective reasons why erstwhile successful students of Japanese may drop the language when they move on to tertiary study. In the current paper, we examine the other core category emerging from our research: the view that 'Japanese and the major are incompatible'. This category considers the academic, institutional and organisational reasons why students feel they are unable to continue with Japanese when they move to tertiary education.